Building Integrated Photovoltaic Thermal Systems : For Sustainable Developments. - Tiwari, G. N.; Agrawal, Basant (Royal Society of Chemistry, The, Ingram Publisher Services [distributor], 2010)
Annotation Solar photovoltaics is one of the most promising renewable energy technologies, producing electricity on site directly from the solar radiation without harming the environment and depletion of materials. The Building Integrated Photovoltaic Thermal (BIPVT) system is a technology which merges PV and thermal systems, simultaneously providing both electric and thermal energy. Through this combination more energy is generated per unit surface area in comparison to the standalone photovoltaics system. Benefits of the BIPVT system include significantly increased electrical performance, faster payback than traditional systems, negligible impact on the environment and the product is easier and less expensive to install with low maintenance required. This book describes the recent developments in PV technologies, solar radiation available on the earth, various BIPVT systems and their applications, energy and exergy analysis, carbondioxide migration and credit earned, life cycle cost analysis and life cycle conversion efficiency. Presently there is no single book which covers all the basic and the advanced concepts related to the implementation of solar energy for the passive heating and cooling of the building. In addition to the basic concepts, the book includes the technology advances, modelling and analysis and ongoing research in the area of BIPVT. Key features of book include: -Solar heating and cooling concepts -Thermal comfort -Performance analysis of BIPVT system -Worldwide case studies -Energy payback period -Techno-economics and sustainability of the system The book, written by experts in the field with years of research and teaching, is intended for the specialists, scientists and people involved in research in the disciplines of renewable energy, energy studies, building energy or carbon credit. For the practicing professional, advanced senior or graduate student with work experience, the book should be used as part of an integrative program enabling them to make deep linkages and thus better decisions in the professional world.
Keywords: Photovoltaic power generation.; Solar batteries.; elektronické knihy; electronic books